MXene combined with β-cyclodextrin stabilized cottonseed oil Pickering emulsions for the preparation of nano-cutting fluids - Wei Wang; Mingan Zhou; Haijiang Xie; Bin Dai; Hualin Lin; Sheng Han (Cleaner Chemical Engineering)
Cutting fluids have long occupied an essential position in industrial manufacturing, but traditional mineral oil-based cutting fluids have limited their application in advanced manufacturing due to hazardous health, non-degradability, and poor thermal conductivity and cleaning ability. To this end, MXene (Ti3C2) was combined with oil-in-water (O/W) Pickering emulsion prepared from β-cyclodextrin-stabilized cottonseed oil to develop a new, highly efficient, environmentally friendly nano-cutting fluid. Among them, β-cyclodextrin, a cyclic oligosaccharide, can be employed as Pickering particles to improve the antioxidant and emulsion stability of cottonseed oil; MXene, an emerging class of 2D nanomaterials possessing excellent lubricating properties, mechanical properties, and thermal stability, is an ideal material for the preparation of high-performance nano-cutting fluids. Optimized by the response surface design, the prepared Pickering emulsion with MXene (0.1wt.%) remained stable for about a month without delamination and improved the thermal conductivity by 136.4 % compared to cottonseed oil. Meanwhile, the coefficient of friction (COF), wear spot diameter (WSD), and tapping torque of Pickering emulsion with MXene were reduced by 35.64 %, 10.90 %, and 17.13 %, respectively, compared with cottonseed oil, and also outperformed commercial cutting fluids. The reduction is attributed to the fact that the oxygen functional groups on the surface of MXene can form hydrogen bonds, which are adsorbed on the friction side to form a strong and dense lubricant film.